A fototerapia como mecanismo potencializador no tratamento da obesidade - Aquino Junior, Antonio Eduardo de (Universidade Federal de São Carlos, 2015)
Obesity is a multifactorial disease, which has endogenous and exogenous origin, and it comprises 95% of all cases. One of the treatments takes into account the negative energy balance, which is the ratio between reduction in consumption and increased energy expenditure. The objective of this study was to analyze the effects of phototherapy associated to (low-level laser therapy) concurrent exercise (aerobic / resistance), at moderate intensity in women with exogenous overweight and obesity. Were selected 64 women, with aged 20-40 years, body mass index between 30 and 40 kg/m2, divided into two groups, which were described as: Sham (concurrent exercise + absence of light) and phototherapy (concurrent exercise + presence of light). It is important to note that at no time volunteers know of the absence of light during the process in Sham group. The exercise protocol parameters followed de Piano (2012), Obesity Study Group member (GEO) - UNIFESP. The irradiation parameter was 100mW, 60mW/cm2, 16 minutes of treatment time, at a wavelength of 808nm and applied in the regions: anterior region - abdominal and quadriceps; posterior region - gluteus and biceps femoral, soon after exercise, 3 times per week for 48 weeks. Thus, the association between phototherapy and moderate intensity exercise was effective in relation to clinical obesity situation, reducing the body weight, body fat deposits, lipid profile and the relationship of glycemic profile / insulin levels and decreasing the possibility insulin resistance. Thus, the action of the technology used in the context of clinical obesity is a new mechanism for multidisciplinary clinical practice in the treatment of obesity.
Keywords: Obesidade; Exercício; Laser de baixa intensidade; Obesity; Exercise; Low-level laser therapy; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE